Mobile Learning Usability Evaluation Using Two Adoption Models - Mafunda, Boniswa; Swart, Arthur; Bere, Aaron (IEEE Xplore: Global Engineering Education Conference (EDUCON), 2017)
The Central University of Technology, Free State has introduced the use of e-books as opposed to printed hard-cover textbooks for students. This is in line with international campaigns seeking the adoption of e- books for educational purposes, while reducing the costs of printing material. This study is aimed at developing an Integrated Framework Model for evaluating the usability of e-books in higher education, thereby enhancing mobile learning adoption at a university. Despite the advantages of usability, continuous emphasis is still placed on the gap which exists between software development and usability evaluation. It is for this reason that the results of usability evaluations frequently have little or no significant influence on the software development of mobile learning applications. This paper reports on the results of a pilot study where a questionnaire was developed to evaluate the use of e-books on mobile devices by students in higher education. The sample size consisted of 49 IT students who registered for a Computer Security module during 2015, where the majority were Sesotho speaking. The outcomes of the study may create provision of a framework useful for evaluating mobile learning usability which may subsequently lead to enhanced adoption.
Published Conference Proceedings
Keywords: Mobile learning; task technology fit; technology acceptance model; usability; adoption